The economic lot-sizing problem with remanufacturing: Analysis and an improved algorithm - Pedro Pi\~neyro; Omar Viera (Journal of Remanufacturing, 2015)
We address the economic lot sizing problem with product returns and remanufacturing. For this problem we provide a new theoretical result about the form of the optimal solutions that can be considered a generalization of the well-known zero-inventory property. Based on this result we suggest an optimized version of an existing Tabu Search procedure. The original and the optimized version of the procedure are evaluated on a recent benchmark set of large instances of 52 periods. The numerical experiment carried out shows that both variants of the procedure outperform the solving procedure suggested in the literature in over 90 % of the tested cases and in about tenth of computation time in the worst case.
Keywords: 650; Economic lot-sizing problem; Remanufacturing; Inventory control; Optimization